Acute Lymphoblastic Leukaemia in the Youngest: Haematopoietic Stem Cell Transplantation and Beyond - Balduzzi, Adriana; Buechner, Jochen; Ifversen, Marianne; Dalle, Jean-Hugues; Colita, Anca M.; Bierings, Marc (Frontiers in Pediatrics, 2022)
The ALL SCTped 2012 FORUM (For Omitting Radiation Under Majority age) trial compared outcomes for children ≥4 years of age transplanted for acute lymphoblastic leukaemia (ALL) who were randomized to myeloablation with a total body irradiation (TBI)-based or chemotherapy-based conditioning regimen. The TBI-based preparation was associated with a lower rate of relapse compared with chemoconditioning. Nevertheless, the age considered suitable for TBI was progressively raised over time to spare the most fragile youngest patients from irradiation-related complications. The best approach to use for children <4 years of age remains unclear. Children diagnosed with ALL in their first year of life, defined as infants, have a remarkably poorer prognosis compared with older children. This is largely explained by the biology of their ALL, with infants often carrying a KMT2A gene rearrangement, as well as by their fragility. In contrast, the clinical presentations and biological features of ALL in children >1 year but <4 years often resemble those presented by older children. In this review, we explore the state of the art regarding haematopoietic stem cell transplantation (HSCT) in children <4 years, the preparative regimens available, and new developments in the field that may influence treatment decisions.